Analisis Maslahah Mursalah Terhadap Pemberian Dispensasi Nikah - Hasan, Hamzah; Herman, Muhammad Akbar; Watowiti, Ardiansyah S. (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The aim of this research is to explain the review of Islamic law in determining the age limit for marriage and the application of the principle of maslahah murlah in granting marriage dispensations. This research uses qualitative research with a phenomenological approach, data collection methods using documentation methods with data analysis using the process of collecting, compiling and discussing information contained in written documents. The results of this research show: 1) Early marriage, even though it is legally legal, does not absolutely apply to everyone and in all conditions. This is because under certain conditions that can cause mafsadat (loss), the law can become makruh or even haram. Legal provisions in Islam cannot be separated from the positive and negative values that arise from them. 2) The context in considering maslahah murrasa, the judge's perception regarding marriage dispensation is included in the realm of maslahah khashshah or the individual or personal benefit of the applicant, because marriage dispensation cases include marriage cases that are private and only involve a few individuals, namely the applicants. So there is no consideration of maslahah 'ammah or general benefit for society.